FIRST RECORD OF Neoergasilus japonicus (HARADA, 1930) (COPEPODA: CYCLOPOIDA) INFECTING A FISH SPECIES IN SOUTH AMERICA - MENDES MARQUES, Taisa (2018)
The parasitic copepod Neoergasilus japonicus (Harada, 1930), native to eastern Asia, was collected from Colossoma macropomum (Cuvier, 1818) cultivated in a fish pound in the department of San Martin, Peru in July 2017. The parasite specimens were found attached to the base of the dorsal fin. Neoergasilus japonicus is widespread in different fish species across the world, being in this study recorded for the first time parasitizing a fish in South America. It is probably that exotic fish hosts associated with the fish-culture industry, such us the tilapia, is the responsible for the transportation and introduction into this part of the world.